Analysis of Goods Delivery Routes Using Saving Matrix and Clarke & Wright Savings Methods - Sari, Rahmi M; Christoffel P, junardi; Ishak, Aulia; Tambunan, Mangara M (Jurnal Sistem Teknik Industri, 2025)
Distribution routes are distribution delivery routes that are created taking into account distance traveled, transport equipment capacity, and delivery capacity so that distribution costs are minimal. To date, there are 14 routes with 32 delivery points. Of the 14 existing routes, there are drop points through which several routes pass. So, companies need to evaluate the routes currently used. This problem arises as a result of the increase in shipping capacity over time. The general objective of this final research is to obtain alternative distribution routes in the process of distributing goods and analyze route improvements by comparing company routes and alternative routes obtained using the Saving Matrix and Clarke & Wright Savings methods. The research results showed that alternative distribution routes using the Saving Matrix method experienced an increase in costs of 5.4% from the original costs. Meanwhile, using the Clarke & Wright Savings method, distribution costs decreased by 3.6% per day. The improvement proposal given is an alternative distribution route using the Clarke & Wright Saving method, which has 11 routes and a savings of 3.6%.